Design Methodology of LLC Resonant Converter for PV-Powered Li-Ion Battery Charger - Ahmed Y. Farag; Mohamed Rabah; Khaled A. El-Metwally; Abdelmomen Mahgoub (IEEE Access)
Existing PV-powered Li-ion chargers used in electric vehicles and other standalone applications typically employ pulse-width modulated dc-dc converters for battery charging control. However, these converters suffer from hard switching, resulting in high switching losses and significant electromagnetic interference. To address these issues, the LLC resonant converter is adopted due to its soft-switching capability. Nevertheless, the design of resonant converters becomes challenging, especially under wide input and output voltage ranges as encountered in PV-powered Li-ion chargers. This paper proposes a systematic design methodology for LLC resonant converters tailored for PV-powered Li-ion charging applications. The objective is to ensure zero-voltage switching (ZVS) for the primary-side switching devices while minimizing the resonant tank current. By accounting for the unique characteristics of PV sources and Li-ion batteries, the proposed approach achieves a narrow variation in PV voltage, which results in a narrow converter gain range and enables a more optimal LLC converter design. Compared to existing design methods, the proposed approach demonstrates reduced resonant tank current and lower turn-off current in the primary-side devices, enhancing overall converter efficiency. Both simulation and experimental results validate the effectiveness of the methodology, confirming ZVS for the primary-side switches across the full operating range, along with zero-current switching of the secondary-side rectifiers throughout most of the operating range.